Prebujanje spečega velikana: trajnostna regeneracija stavbe KPD (University of Maribor Press, 2017)
Awakening the Sleeping Giant: Sustainable Regeneration of the KPD Building. The ‘KPD’ building with its important strategic position presents a case of a large underused building in Maribor to be analysed within the scope of the URBACT III - 2nd Chance programme. As an introduction, the paper addresses the problem of the abandoned building and site of the former prison complex that has been carried out as a student project of the architecture master’s study programme 2016-2017. The objective of the multi-layered design process was to create different scenarios for the revitalisation of the ‘KPD’ premises, symbolically called the ‘Sleeping giant’, and to obtain ideas containing diverse and attractive programmes presented in variant solutions for a new image of the degraded area that should motivate various stakeholders. Further, the paper presents a description of the design process of different student ideas, targeted at integrating various functions which the city is lacking. The results of students’ work are summarized in three alternative concepts. The concept “Cultural Centre Maribor” focuses on the functional reorganization of the interior with a minimum of interventions to house various cultural programs. The concept “Market Way” builds on the prevailing program of the existing shopping centre, upgrading it with new developments that create a new attractive portal to the city. The concept “Island Awakening” focuses on the problem of isolation and invisibility of the complex in relation to the city centre. The vision of designing a new green city centre is based on the creation of the new platform across the city road.